Creating River North: A Case Study of Demographic Shifts in Denver - Lechuga, Anthony. (2017)
Abstract: The City of Denver has undergone rapid population growth since the year 2000. In light of this growth, my research explores what policies and plans may have affected demographic shifts in the area of River North. Analysis of racial demographics of the area shows extensive absolute population growth of the Non-Hispanic White population and absolute declining populations for every other demographic. My analysis found a moderately strong correlation between new building projects, the decline of Hispanic populations, and the rise of Non-Hispanic White populations. In 2003, Denver released the River North Plan for the redevelopment of an area that was historically industrial. Consequently, local artists formed the River North Art District. With approval from the Denver government, the Art District has grown to include oversight of a Business Improvement District and General Improvement District. In this way, the city has placed great power with the elected board of a local non-profit agency that oversees programming, design, and development of the area, many of whom are interviewed in my research as part of understanding their role and responsibilities. Simultaneously the government created an Inclusionary Housing Ordinance that produced no new housing in River North between 2000-2015. Denver's actions have unintentionally created powers that encourage processes of, without creating measures for avoiding, gentrification-induced displacement.; Thesis (M.A.)--Tufts University, 2017.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Julian Agyeman.; Committee: Justin Hollander.; Keyword: Urban planning.